Sistem Pendukung Keputusan Program Kerja Pengawasan Tahunan Menggunakan Metode Simple Additive Weighting - Indra Gunawan; Julius Santony; S Sumijan (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
The Annual Supervision Work Program (ASWP) is a measure of efficiency and effectiveness in implementing supervision in supporting Inspectorate performance. For the preparation of this ASWP using a Risk-Based Supervision Planning (RBSP) based on certain criteria. Decision Support System (DSS) is a system used to determine alternative ASWP to be implemented. The criteria are determined using the Simple Additive Weighting (SAW) method. The basic concept of the SAW method is to find the total weighting of the performance rating for each alternative. Testing is done from ASWP alternative normalized according to the type of attribute criteria (benefit or cost). The final result is obtained from the calculation process, namely from the 10 test data there is 80% compatibility of the data from the system calculation. The sum of the normalized matrix with weights per criterion shows an alternative ranking of the regional apparatus organization that is closest to the criteria to the most distant from the criteria. In order to get an alternative ASWP to be implemented.